Proposal of new genera and species of the subfamily Diosaccinae (Copepoda: Harpacticoida: Miraciidae) – Corrigendum - Gómez, Samuel; Corgosinho, Paulo Henrique Costa; Rivera-Sánchez, Karen I. (European Journal of Taxonomy, 2021)
The present corrigendum corrects errors that occurred in Gómez S., Corgosinho P.H.C. & Rivera-Sánchez K.I. 2021. Proposal of new genera and species of the subfamily Diosaccinae (Copepoda : Harpacticoida : Miraciidae). European Journal of Taxonomy 759 : 1–62. https://doi.org/10.5852/ejt.2021.759.1433